Screen printed PLZT thick films prepared from nanopowders - Stojanovic, B. D.; Mitic, V.; Pejovic, V.; Vijatovic, M. M.; Zaghete, M. A. (Elsevier B.V., 2007)
The gap between the bulk materials and thin films can be filled with thick films suitably designed and appropriate processed. Thick films of complex system like lead-lanthanum-zirconium titanate (PLZT) is difficult to produce by simple solid-state reaction keeping compositional homogeneity and optimal grain size distribution. In the present work, PLZT thick films were fabricated by screen-printing technique from nanosized powders obtained through soft chemistry by polymeric precursor method. Thick film paste was obtained by mixing PLZT fine powders and organic vehicle. The upper and bottom electrodes based on Ag-Pd and functional component based on PLZT were screen-printed on alumina substrate and after that annealed in air atmosphere. The powder morphology, microstructure, dielectric and ferroelectric properties of 9.5/65/35 PLZT thick films were analysed. (c) 2007 Elsevier Ltd. All rights reserved.
Keywords: films; electron microscopy; dielectric properties; ferroelectric properties; PLZT